Strategies and Segments on the Performance of Retail Companies in Indonesia during the Covid Pandemic - Mombang Sihite; Nurmala Ahmar; Yuyun Sunhayati (International Journal of Social Service and Research, 2023)
The abstract contains a brief description of the purpose: describes the objectives and hypotheses of the research. Methods: describes the essential features of the research design, data, and analysis. It may include the sample size, geographic location, demographics, variables, controls, conditions, tests, descriptions of research design, details of sampling techniques, and data gathering procedures. Results: describes the key findings of the study, including experimental, correlational, or theoretical results. It may also provide a brief explanation of the results. Implications: show how the results connect to policy and practice and provide suggestions for follow-up, future studies, or further analysis. Additional materials: notes the number of references, tables, graphs, exhibits, test instruments, appendixes, or other supplemental materials in the paper. Also, the abstract must be written in a single paragraph in English, max 250 words.